PATHOTYPE GROUPING OF Xanthomonas oryzae pv. oryzae ISOLATES FROM SOUTH SULAWESI AND SOUTHEAST SULAWESI - Khaeruni, Andi; Wijayanto, Teguh (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2013)
Bacterial leaf blight caused by Xanthomonas oryzae pv. oryzae (Xoo) is an important rice disease, and has caused significant economic losses. This research aimed to determine the pathotype grouping and the distribution of Xoo isolates of South and Southeast Sulawesi. In order to obtain the information, 61 Xoo isolates of South Sulawesi and 29 isolates of Southeast Sulawesi were evaluated for their pathotype grouping against 5 diffential varieties. Research results showed that in South Sulawesi there were 2 pathotype groups, namely pathotype IV (32.79%) and pathotype VIII(67.21%). Pathotype VIII was widely distributed over the Western and Central areas of South Sulawesi, whereas pathotype IV was widely distributed over the Southern area. In Southeast Sulawesi, it was found 5 pathotypes, namely pathotypes IV (27.58%), VI (10.34%), VIII (13.79%), IX (20.68%), and X (27.58%), with a limited and scattered distribution pattern on several areas. These results indicate that Xoo pathotype groups in South Sulawesi and Southeast Sulawesi are varied and tend to sift to more virulent pathotypes. Keywords: bacterial leaf blight, pathotype group, Xanthomonas oryzae pv. oryzae